2020
DOI: 10.1093/jncics/pkaa005
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Incidence Trends by Estrogen Receptor Status Among Asian American Ethnic Groups, 1990–2014

Abstract: Background Westernization and etiologic heterogeneity may play a role in the rising breast cancer incidence in Asian American (AA) women. We report breast cancer incidence in Asian-origin populations. Methods Using a specialized Surveillance, Epidemiology, and End Results-9 Plus API Database (1990–2014), we analyzed breast cancer incidence overall, by estrogen receptor (ER) status, and age group among non-Hispanic white (NHW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…This is in contrast to an APC of 1.1% among Chinese (95% CI, 0.7–1.5) and Filipinas (95% CI, 0.7–1.4), with no significant increase observed for Japanese women during this period. Another study by Tuan et al 14 similarly found an increase in BC incidence rate between 1990 and 2014 among Chinese, South Asian (Asian Indians and Pakistani), Korean, Vietnamese, and Filipino women, with no such trends seen in NHW or Japanese women.…”
Section: Breast Cancer Incidencementioning
confidence: 95%
“…This is in contrast to an APC of 1.1% among Chinese (95% CI, 0.7–1.5) and Filipinas (95% CI, 0.7–1.4), with no significant increase observed for Japanese women during this period. Another study by Tuan et al 14 similarly found an increase in BC incidence rate between 1990 and 2014 among Chinese, South Asian (Asian Indians and Pakistani), Korean, Vietnamese, and Filipino women, with no such trends seen in NHW or Japanese women.…”
Section: Breast Cancer Incidencementioning
confidence: 95%
“…Breast cancer is the second leading cause of death among Asian women in the United States, as well as the most commonly diagnosed cancer among women of Korean descent in America (American Cancer Society, 2016). Korean and Korean American women experience one of the highest rates of breast cancer incidence among Asian American women (Torre et al, 2016; Tuan et al, 2020). Yet, women of Korean descent have biannual mammography rates ranging from 36% to 65% which are lower than most other racial groups in the United States (American Cancer Society, 2016; S.…”
Section: Introductionmentioning
confidence: 99%
“…A study using the SEER Asian Pacific Islander Database (1990Database ( -2014 reported that Korean American women (KAW) have one of the highest breast cancer incidence rate increases (2.55% per year) compared to other Asian American women (Tuan et al, 2020). Despite the increasing burden of breast cancer diagnosis, screening rates among KAW remain low.…”
Section: Introductionmentioning
confidence: 99%